Assessment of microbiological status of fresh gilthead seabream (Sparus aurata) from aquaculture in Adriatic sea, Montenegro Microbiology of gilthead seabream - Grkovic, N; Bogdanovic, IZ; Djurić, S; Čobanović, N; Suvajdžić, B; Vićić, I; Karabasil, N; Dimitrijevic, M (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this research was to determine the microbiological status of gilthead seabream (Sparus aurata), which were caught in the Boka Kotorska Bay (Montenegro), for the first time in this part of . Collected fish were analysed for hygiene indicator and pathogens microorganisms through the winter and summer season during one year. Total bacterial counts of aerobic mesophilic bacteria (AB), Enterobacteriaceae, Salmonella spp., Escherichia coli, coagulase-positive Staphylococci (CoPS) and sulphite-reducing Clostridia (SRC) were measured. Results shown that all samples were suitable for human consumption in terms of microbiology status. The microbiological quality of individual samples varied widely between winter/summer seasons regarding total counts of aerobic mesophilic and Enterobacteriaceae. Samples obtained in summer showed significantly higher levels for aerobic mesophilic bacteria and Enterobacteriaceae then samples obtained in winter. Salmonella spp. and E. coli were not detected in fish samples, and also none of the samples tested for coagulase positive Staphylococci and sulphite-reducing Clostridia were above the detection limit (10 CFU/g). Results underline the relevance of preventing and the application of good hygiene and good manufacturing practice during fish handling to secure the quality and safety of sea bream. Also, results presented in this study is valuable in the assessment of conditions in aquatic environments and and this method of testing can be applied in other locations worldwide.